A Systematic Review About the Contribution of The Genus Tessaria (Asteraceae) To Cancer Study and Treatment - Sosa-Lochedino, Arianna (2022)
Belonging to the Asteraceae family, Tessaria (Ruiz & Pavon, 1753) is a genus of shrubs or small trees distributed in various habitats located from Argentina to the southwestern United States of America. The taxa are composed of five confirmed species, which have been previously reported for their ethnopharmacological uses as hypocholesterolemiant, hypoglycemic, antitussive, anti-inflammatory, anticancer, and abortifacient agent; it also has been used in hepatic, renal, pulmonary, and rheumatic diseases. Up to the present, T. absinthioides, T. ambigua, T. dodoneifolia, T. fastigiata and T. integrifolia have been chemically analyzed. While decoctions, infusions, methanolic, and hydromethanolic extracts are the most studied botanical compounds, its most recognized phytochemical constituents are caffeoylquinic acid, eupatorin, naringenin, protocatechuic, and quercetin. Scientifically, several biomedical properties such as virucidal, antibacterial, leishmanicidal, insecticidal, gastroprotective, antiasthmatic, hypoglycemic, and antiatherogenic were attributed to the genus. Concerning oncologic research, the chemicals produced by Tessaria have antitumor activities interfering with carcinogenesis, cell proliferation, metastasis, and angiogenesis. In addition, the natural extracts obtained from Tessaria species have biological activities closely related to cancer, acting as antioxidants and anti-inflammatories. In particular, it has been reported that T. absinthioides resulted cytotoxic against several cancer cell lines and acts as an antitumoral compound in murine models. Due to the aforementioned antecedents, the Tessaria species are considered undervalued within the oncological field; the goal of the current systematic review is to summarize the information available on the genus, relevant for cancer research and treatment.